Effect of acid modification on the material and compaction properties of fonio and sweet potato starches (2014)
Starches obtained from the grains of white fonio (Digitaria exilis) and tubers of sweet potato (Ipomea batatas) have been modified by acid hydrolysis at different steeping times – (0, 24 and 96 h) and the physicochemical, material and compaction properties of the modified starches have been evaluated in comparison with official corn starch. The effect of acid modification on the compaction properties of the starches were evaluated with the aim of determining their usefulness as excipients in direct compression. The results showed that the physicochemical and material properties of the starches varied considerably depending on their botanical source. Acid modification led to an increase in solubility and relative crystallinity but decrease in swelling and viscosity of the starches. The effects were found to depend on the steeping time during acid hydrolysis. The results of the compressional properties indicated that the starches formed intact tablets at relatively low compression pressure with acid modified starches forming tablets with higher tensile strength than the natural starches. The results indicate that the physicochemical and compaction properties of white fonio and sweet potato starches were improved by acidmodification yielding starches that could be suitable as directly compressible excipient.